Optimization of Process Parameters for Removal of Arsenic Using Activated Carbon-Based Iron-Containing Adsorbents by Response Surface Methodology - Tuna, Asli Ozge Avci; Ozdemir, Ercan; Simsek, Esra Bilgin; Beker, Ulker (SPRINGER INTERNATIONAL PUBLISHING AG, 2013)
In this study, arsenate removal by apricot stone-based activated carbon (IAC) modified with iron (oxy-hydr)oxides was carried out. For this purpose, hybrid adsorbents based on Fe2+-loaded activated carbon (IAC-Fe(II)) and Fe3+-loaded activated carbon (IAC-Fe(III)) were synthesized by precipitation method. A three-level, three-factor Box-Behnken experimental design combined with response surface methodology (RSM) was employed to find the optimum combination of process parameters for maximizing the As(V) adsorption capacity of activated carbon-based iron-containing hybrid adsorbent. Three important operation parameters, namely, initial pH of solution (3.0-7.0), temperature (25-65 degrees C), and initial As(V) concentration (0.5-8.5 mg L-1), were chosen as the independent variables, while the As(V) adsorption capacities of hybrid adsorbents were designated as dependent variables. Lack of fit test showed that the quadratic model provided the best fit to experimental data for both adsorbents with the highest coefficients of determination (R-2), adjusted R-2, and p-values for lack of fit. The standardized effects of the independent variables and their interactions were tested by analysis of variance and Pareto chart. The model F-values (F (IAC-Fe(II))=330.39 and F (IAC-Fe(III))=36.19) and R-2 values (R-2 IAC-Fe(II)=0.9977 and R-2 (IAC-Fe(III))=0.9789) of second-order polynomial regression equations indicated the significance of the regression models. Optimum process conditions for As(V) adsorption onto IAC-Fe(II) were 63.68 degrees C, pH 3.10, and 8.4 mg L-1 initial arsenic concentration, while 25.22 degrees C, pH 3.07, and 8.28 mg L-1 initial As(V) concentration were found to be optimum conditions for IAC-Fe(III).
Keywords: Activated carbon; Iron (oxy-hydr) oxides; Arsenic; Box-Behnken; Response surface methodology; AQUEOUS-SOLUTION; AS(V) REMOVAL; GROUND-WATER; ADSORPTION; ION; CHEMISTRY; MANGANESE; LEAD(II); BEHAVIOR; SULFATE; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources